(untitled) (Journal of Hama University, 2022)
The study aims at finding out the effect of work environment on administrative creativity in Lattakia textile Company. The descriptive method has been adopted by the researcher. The research sample consists of 45 questionnaires which have been distributed among the management staff in the administration of the company (upper, intermediate and lower). 42 questionnaires have been returned, of which 2 have been found invalid, leaving 40 valid questionnaires. The following results have been achieved by the researcher: There is an influence of work environment, as represented by organization framework, regulation and measures, training, taking part in decision making, incentives and rewards on administrative creativity. On the other hand, a slight relationship has been found out between the ’working conditions’ dimension and administrative creativity, which can be result of the current situation in our country, which, in turn, has led to a weak influence of this dimension (working conditions) on administrative creativity in the studied company in terms of providing the requirements for professional security and offering the required working materials.